Should we welcome plans to sell off NHS land?. (27th September 2017) - Naylor, Robert; Chand, Kailash
Abstract : The government seems likely to back the recommendations of Robert Naylor to raise capital by selling off inefficiently used assets, but Kailash Chand worries that services could be threatened and that public consultation is lacking